MODERN ASPECTS OF SURGICAL TREATMENT AND DIAGNOSIS OF COLORECTAL CANCER - Professor. Tillyashaikhov Mirzagolib Nigmatovich; K.m.n. Rakhimov Okiljon Abdukhalilovich; D.m.n. associate professor Adilhodzhaev Askar Anvarovich; K.m.n. Akhmedov Odiljon Muhamedzhanovich; Makhkamov Tahir Khakimovich (Scholar Express Journals, 2024)
Today, colorectal cancer remains the most common malignant neoplasm, the main method of which is surgical treatment. According to Global Cancer Statistics, in 2020, the mortality rate from colorectal cancer was 9.4%, and the number of new cases was about 2 million.
Keywords: Colorectal cancer; colon resection; rehabilitation